2001
DOI: 10.4319/lo.2001.46.1.0178
|View full text |Cite
|
Sign up to set email alerts
|

A whole‐basin study of sediment accumulation using stable lead isotopes and flyash particles in an acidified lake, Sweden

Abstract: Using analyses of lead concentrations, lead isotopes ( 206 Pb/ 207 Pb), and spheroidal carbonaceous flyash particles (SCP), we studied sediment accumulation patterns in the acidified lake Härsvatten in southwest Sweden. After determining the natural background 206 Pb/ 207 Pb ratio (1.5) in deeper sediments in long sediment cores from three basins in the lake, we applied an isotope mixing model to quantify pollution Pb accumulation in 46 gravity cores. The mean pollution Pb inventory in the cores was 2.6 g m Ϫ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…In Sweden, the sediments up to 3500 BP had consistently high 206 Pb/ 207 Pb ratios in the range of 1.3 to 2.0 Bindler et al 2001Bindler et al , 2009Brännvall et al 2001a). …”
Section: Historical Lead Pollution and Lead Deposition Rates In Swedenmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, the sediments up to 3500 BP had consistently high 206 Pb/ 207 Pb ratios in the range of 1.3 to 2.0 Bindler et al 2001Bindler et al , 2009Brännvall et al 2001a). …”
Section: Historical Lead Pollution and Lead Deposition Rates In Swedenmentioning
confidence: 99%
“…1). These archives include lake sediments in Sweden (Renberg et al 1994;Brännvall et al 1999Brännvall et al , 2001aBindler et al 2001); peat deposits in Sweden Klaminder et al 2003), Spain (Martínez-Cortizas et al 2002;Kylander et al 2005), France (Monna et al 2004a, b;Baron et al 2005), Belgium (De Vleeschouwer et al 2007), Switzerland (Shotyk et al 1998), Germany (Le Roux et al 2005, the UK (Le Roux et al 2004;Cloy et al 2008), and Iceland (Marshall et al 2009); and ice records from Greenland and Devon Island (Hong et al 1994;Rosman et al 1997;Zheng et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, results from our two multiple-core lakes demonstrated that the OC : Pb with fine-grained sediment particles, including organic seston. However, OC from littoral production and particulate carbon from terrestrial sources might focus differently than 210 Pb because of spatially non-uniform loading, especially in complex lake basins with multiple embayments (Bindler et al 2001;Engstrom and Rose 2013). Nonetheless, the relative uniformity of OC: 210 Pb ratios noted above suggests that both constituents are redistributed to the depositional region of a lake in roughly the same proportions.…”
Section: Hobbs Et Almentioning
confidence: 99%
“…Finally, the zone of sediment erosion (ZSE), located in high-energy, shallow environments, is characterized by coarse-grained, dense inorganic sediments and low sediment-accretion rates. This pattern, however, does not hold where the littoral zone is colonized by submerged vegetation (James and Barko 1990;Benoy and Kalff 1999;Bindler et al 2001).…”
mentioning
confidence: 99%